Vaccine strategies for prevention of community-acquired pneumonia in Canada: Who would benefit most from pneumococcal immunization? - Kaplan, Alan (Can Fam Physician, 2019)
OBJECTIVE: To describe the burden of pneumococcal disease and associated risk factors in the Canadian adult population, delineate available pneumococcal vaccines and associated efficacy and effectiveness data, and review current pneumococcal vaccine recommendations and community-acquired pneumonia (CAP) prevention strategies in Canada. QUALITY OF EVIDENCE: Pneumococcal vaccination guidelines from the Canadian National Advisory Committee on Immunization in 2013 and 2016 constitute level III evidence for CAP prevention in the Canadian adult population. MAIN MESSAGE: It is recommended that immunosuppressed adults of all ages receive the 13-valent pneumococcal conjugate vaccine (PCV13) (grades A and B recommendations). In 2016, the National Advisory Committee on Immunization also recommended that all adults aged 65 years and older receive PCV13 (grade A recommendation) on an individual basis, followed by the 23-valent pneumococcal polysaccharide vaccine (grade B recommendation). This update is based on a large clinical study that demonstrated PCV13 efficacy against vaccine-type CAP in this population. CONCLUSION: Physicians should focus on improving pneumococcal vaccination rates among adults, which remain low. Vaccination with PCV13 should also be considered for adults with chronic conditions, whose baseline risk is often higher than that for healthy individuals aged 65 years and older.